Studies of fish community from predeltaic area (Somova-Parcheş lake-complex) in 2009 - OȚEL Vasile; NĂSTASE Aurel (Scientific Annals of the Danube Delta Institute, 2011)
The status of fish fauna from predeltaic area (Somova-Parches lake-complex from DDBR, Romania)is described in this paper. Fish community was sampled in 2009 and for sampling were used two complementary methods: electric fishing for shallow border zone and Nordic gillnet fishing for deep open water. The frequency ofoccurrence and the dominance in abundance analysis was based on 44 samples including 5,372 individuals since the dominance in biomass was based on almost 96 kg from both sampling methods. In total was captured 31 fish species, while commercial fish species (with high and second food economical values) which catch statistics recorded 14 commercial species. Unlike the 2003 and 2006 studies years wasn’t found very rare species S. volgensis in complex also in all DDBR, instead was first recorded in complex of species - P. glenii, but others species was captured goby species and S. abaster. In the sampling analysis, very frequent species were bleak, perch, roach, rudd and white bream. The most abundant (eudominant and dominant) species were bleak, roach, rudd, perch and white bream. In biomass dominate roach, gibel carp, perch, white bream and pike. The main species, eudominant and euconstant species were roach and bleak, followed by characteristic or complementary, eudominant and euconstant species like rudd and perch, but for other side accidental, sporadic and very rare species in capture in 2009 period of sampling were L. delineatus, M. fossilis, N. gymnotrachelus, N. kessleri, C. carpio, T. tinca and S. glanis. Ichthyodiversity indices show a stable fish ecosystem for both zones of study (border zone and open water zone). Fish analysis, like in all Danube delta lakes, in predeltaic area is also dominated by small or medium size eurytopic and opportunistic species also, favoured by eutrophication of lakes. Experimental fishing, which analyzed status of fish fauna, is completed with commercial statistics from professional fishermen, what makes both analysis (experimental fishing and catch statistics stock) together to be valuable tools in sustainable management of fish resources and for promoting conservation of fish diversity in complex. This paper describes just fish analyzed from experimental fishing.